LEGAL REVIEW OF ONLINE GAMBLING CRIMES IN INDONESIA ACCORDING TO LAW NUMBER 11 OF 2008 CONCERNING ELECTRONIC INFORMATION AND TRANSACTIONS - Novan Trianda Matondang; Henry Aspan; T. Riza Zarzani (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Modern developments that drive advancements in technology and the internet have had a positive impact on society. People can easily access everything available on electronic media. However, the development of internet-based electronic media can also have negative impacts, such as the emergence of new social problems, namely the emergence of online gambling cases. Online gambling is a form of betting between players using money as the wager determined by the player and the online gambler, conducted on electronic media connected to the internet. Online gambling is illegal and violates existing societal values ​​and norms. The type of research used in this journal is normative juridical legal research, which emphasizes efforts to find and analyze legal rules, legal principles, and legal doctrines, including the objectives of law and applicable values ​​of justice. The analytical method applied uses a deductive reasoning approach, by collecting information and data through the study of relevant legal literature. What are the legal provisions for criminal acts of gambling via the internet according to Law Number 11 of 2008 concerning Information and Electronic Transactions? What is the criminal responsibility for online gambling using the internet according to Law Number 11 of 2008 concerning Information and Electronic Transactions. Therefore, there is a need for strict criminal sanctions imposed on online gambling perpetrators. The provisions for criminal acts for online gambling perpetrators in Indonesia are regulated in Article 303 bis of the Criminal Code, Article 2 paragraphs (1), (2), (3) of Law No. 7 of 1974 concerning Gambling Publication and Article 27 paragraph 2 Jo. Article 45 paragraph 2 of the ITE Law